Intensification of the process of plasma-induction growing of large profiled tungsten single crystals - Shapovalov, V.O.; Gnizdylo, O.M.; Yakusha, V.V.; Nikitenko, Yu.O.; Berdnikova, E.M.; Khohlova, J.A. (Вопросы атомной науки и техники, 2022)
The structure of a profiled tungsten single crystal obtained by plasma-induction layer-by-layer growth on a single crystal seed crystal at different deposition rates is investigated. Investigated – microhardness, size of the subgrain structure, angles of misorientation of subgrains, the nature of the distribution of dislocations, etc. A complex of experimental methods of modern physical materials science was used, including light, scanning and transmission microdiffraction electron microscopy. It was found that the ingot is a single crystal body with a crystallographic orientation given by the seed crystal. An increase in the growth rate to 70 mm/min leads to an insignificant decrease in microhardness, refinement of the substructure with a uniform distribution of the dislocation density, which makes it possible to obtain tungsten single crystals with a single crystal structure at disorientation angles not exceeding 3°.